Impact of Rising Tourism Industry On Impedence of Indian Economy - Kumar, Dr. Yogendra (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
Tourism industry is one of the largest industries in the world. It generates wealth and employment. It is one of the important foreign exchange earnings industries in India. It is also plays an important role in the contribution of GDP in Indian economy. Tourism refers to the process of travelling to different places internationally or domestically. The present paper discusses the impact of tourism industry on Indian economy and the study is based on fully secondary data. The variables are assessed with the help of correlation. Keywords- Foreign Tourist Arrivals (FTAs), Domestic Tourist Arrivals(DTAs), GDP, Foreign Exchange Earnings(FEEs).